2011
DOI: 10.1097/aud.0b013e31822229d3
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis of Speech-in-Noise Perception in Older Adults

Abstract: Objective We investigated a neural basis of speech-in-noise perception in older adults. Hearing loss, the third most common chronic condition in older adults, is most often manifested by difficulty with understanding speech in background noise. This trouble with understanding speech in noise, which occurs even in individuals who have normal hearing thresholds, may arise, in part, from age-related declines in central auditory processing of the temporal and spectral components of speech. We hypothesized that old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(214 citation statements)
references
References 77 publications
(84 reference statements)
7
182
4
2
Order By: Relevance
“…In contrast to our results, some past studies have demonstrated that additive acoustic noise degrades the FFR ENV response, including at F 0 (e.g., Anderson et al, 2011); however, the size of the effect of additive noise on FFR ENV appears to depend not only on the acoustic properties of the signal and noise, but also on other factors, such as perceptual abilities that can vary across listeners (e.g., see Cunningham et al, 2001;Song et al, 2011). We do not know of any studies of the effects of additive acoustic noise on FFR ENV that used exactly the same stimuli as we employed here (harmonic complexes consisting of the first eight harmonics of 100 Hz, at equal intensity; broadband Gaussian noise).…”
Section: Contrasting the Neural Response At F 0 To Other Neural Cocontrasting
confidence: 55%
“…In contrast to our results, some past studies have demonstrated that additive acoustic noise degrades the FFR ENV response, including at F 0 (e.g., Anderson et al, 2011); however, the size of the effect of additive noise on FFR ENV appears to depend not only on the acoustic properties of the signal and noise, but also on other factors, such as perceptual abilities that can vary across listeners (e.g., see Cunningham et al, 2001;Song et al, 2011). We do not know of any studies of the effects of additive acoustic noise on FFR ENV that used exactly the same stimuli as we employed here (harmonic complexes consisting of the first eight harmonics of 100 Hz, at equal intensity; broadband Gaussian noise).…”
Section: Contrasting the Neural Response At F 0 To Other Neural Cocontrasting
confidence: 55%
“…Cognition has emerged as an important concept in the context of speech perception and comprehension in the last fifty years (e.g., Rabbitt, 1968;Rönnberg et al, 2013;Schneider, 2011;van Rooij & Plomp, 1990, 1992Wingfield, Tun, & McCoy, 2005), partly to account for finding that listeners with similar hearing impairments can vary widely in their level of functioning (Anderson, Parbery-Clark, Yi, & Kraus, 2011;GordonSalant & Fitzgibbons, 1993;Vermiglio, Soli, Freed, & Fisher, 2012). Cognition is a multi-faceted concept and in the following section we will limit the discussion of agerelated cognitive changes to those aspects that are most likely to affect spoken-language comprehension.…”
Section: Attentional Functions (B140)mentioning
confidence: 99%
“…Abnormalities in the speech ABR have been repeatedly correlated with deficits in speech-in noise perception, particularly in aging populations (Anderson et al 2011(Anderson et al , 2012Ruggles et al 2012) and in children, usually with language-related learning problems (Anderson et al 2010b;Hornickel et al 2011;Hornickel and Kraus 2013). A peripheral basis for these abnormalities in terms of hearing sensitivity has generally been ruled out, because the participant groups tested presented clinically normal audiograms.…”
mentioning
confidence: 99%